KONSEP PENDIDIKAN ISLAM MENURUT AL-QURAN SURAT AL FATH AYAT 29 DAN IMPLEMENTASINYA TERHADAP PROFESIONALISME GURU PAI - Abdul Haris (Program Pascasarjana Institut Agama Islam Tasikmalaya, 2023)
Abstract Teachers are the dominant and most important factor in formal education in general, because for students, teachers are role models, role models and even become self-identification figures. Therefore, teachers should have adequate traits, behaviors and abilities to develop students as a whole in this case said to be a professional teacher. This research aims to find out how the criteria of Islamic Education teachers in QS Al-Fath verse 29, how the implications of QS Al-Fath verse 29 towards improving teacher professionalism, the values of teacher professionalism. The method used is descriptive method. Descriptive method is one way or presentation of work and descriptive is to use something according to the existing state of facts. The results of this study are the criteria for Islamic education teachers based on QS Al-Fath verse 29 that a teacher must have an Islamic personality, be firm, be a role model and role model for students, have high insight and know child psychology and be able to communicate well with students. The implication of Surah Al-Fath verse 29 on teacher professionalism is that a teacher must be tough on anyone who opposes religion, and is compassionate to fellow educators and students as well as all components of teaching and learning activities in the educational environment, has spiritual competence to make religion an application of science, especially religious science and devotes himself to God, religion, nation and state and the values of teacher professionalism contained in Al-Quran Surah Al-Fath verse 29 that every leader or educator should have a firm attitude, The values of professionalism of teachers contained in the Al-Quran letter Al-Fath verse 29 that every leader or educator should have a firm attitude, authoritative, and hard in defending the principles of Islam, especially those related to the issue of faith or the basic principles of Islam, have spiritual competence, make worship, especially worship makdhoh as a foundation and also a way to get closer to Allah in order to always get His guidance and taufik in carrying out their duties as educators